Irony as Trauma & Trauma as Irony in Claude Lanzmann’s Shoah - Bhubaneswari, T.S.; Singh, Ajeet (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
Claude Lanzmann makes use of what this essay posits as metairony which dramatizes the shocks of the acting out of the trauma of the Holocaust. The film director makes the survivors and witnesses and the viewers to become retraumatized and to relive the past. By so doing, the traumatized mind can cope with the trauma because acting out helps the reflective consciousness to prevent itself from being overwhelmed by shock, in Walter Benjamin’s assumption, by reproducing shock, that is, by seizing upon each traumatic moment and parrying it - in effect, by responding to violence with violence. Testimonies in Shoah break the boundary between the experience of shock and experience as shock.